Alien [videorecording (DVD)] - Scott, Ridley; Skerritt, Tom; Weaver, Sigourney, 1949-; Cartwright, Veronica; Stanton, Harry Dean, 1926-2017; Hurt, John, 1940-2017 (Twentieth Century Fox Home Entertainment, 2017)
After responding to a signal for help, a spaceship takes on an alien creature which begins to kill the crew.